Sulfur isotope anomalies (Δ33S) in urban air pollution linked to mineral-dust-associated sulfateclick to copy article link - Dasari, S; Paris, G; Saar, B; Pei, Q; Cong, Z; Widory, D (American Chemical Society, 2022)
Sulfur isotope analysis provides a unique probe for source-specific information and certain atmospheric reactions. Globally, atmospheric aerosols in urban locations exhibit significant sulfur mass-independent fractionation (i.e., S-MIF, Δ33S ≠ 0). The origin(s) of these S-MIF anomalies remains unclear, thereby limiting the interpretation and/or application of such signals. Here, we conducted dual-isotope (Δ33S and δ34S) fingerprinting of sulfate aerosols from summertime megacity Delhi in south Asia. A shift toward concomitantly high Δ33S (from 0.2‰ to 0.5‰) and low δ34S (from 5‰ to 1‰) values was observed with the influx of mineral dust. The Fe:Al ratio showed significant correlations with both sulfate loadings (R2 = 0.84) and Δ33S signatures (R2 = 0.77). Contrary to the prevailing paradigm, this observational evidence suggests that mineral-dust-associated sulfate exhibits S-MIF anomalies. Atmospheric processing of mineral dust plausibly leads to the production of these anomalies. Our evaluation suggests that an inherent mechanism(s) remains elusive. Although hindered by end-member uncertainties, we show that S-MIF signals can be source apportioned to quantitatively constrain the fraction of mineral-dust-associated sulfate in urban locations. The influx of mineral-dust-associated sulfate can influence urban air pollution affecting air quality and/or human health and as such requires monitoring. Urban Δ33S signals can therefore be used to trace this sulfate fraction, thereby improving our understanding of sulfate aerosol dynamics.